Perceptions of rock band musicians about the effects of loud music and protective practices - Rodrigues, Matilde (2015)
Rock band musicians are an important group in what regards to the exposure to high sound pressure levels. They can be exposed to loud music, which can result in hearing damages. However, there are very few studies focused on this issue. In view of this, this study attempts to analyze the perceptions about musicians in relation to the loud music risks, as well as to characterize their preventive behaviors and health effects. To analyze this issue, a questionnaire was applied to 14 musicians belonging to three garage rock bands. The results showed that group rehearsals and concerts are considered the noisiest activities and the sound pressure levels at individual practices are seen as low. Guitar and drums were identified as the noisiest instruments and the piano was seen as the instrument that produce lower sound levels. The results also showed that only a part of the musicians were concerned with the health effects related to the exposure to high sound levels and the majority of them reported do not use hearing protection. The findings of this study emphasize the need to give more attention to these groups, informing them about the risks and on the need of risk reduction measures.